A Rare Case of Autoimmune Pancreatitis in a 9-Year-Old Male Patient: A Comprehensive Diagnosis and Successful Treatment - Hadi Farhat; Christie Dib; Yehya Tlaiss; Ayman Tabcheh; Pierre Hani (Case Reports in Gastrointestinal Medicine)
Autoimmune pancreatitis (AIP) is a rare and complex condition that can be difficult to identify due to its resemblance to malignancies. This case report presents a unique instance of AIP in a 9-year-old male patient who presented with painless jaundice and elevated liver function test results. His symptoms were persistent even after previous common bile duct stent placement, requiring additional investigation. The possibility of AIP was raised by further serological tests and imaging examinations. The diagnosis was then confirmed by multiple characteristic findings revealed through history, imaging, clinical examination, histology, and lab results. Treatment was initiated with corticosteroids, which resulted in a complete resolution of symptoms and remarkable recovery. This case emphasizes the significance of including AIP in the differential diagnosis of pancreatic disorders, even in pediatric patients.